Pulmonary valve endocarditis in adults with congenital heart disease: the role of echocardiography in a case series. Issue 5 (19th September 2020) - Fusco, Flavia; Scognamiglio, Giancarlo; Correra, Anna; Merola, Assunta; Colonna, Diego; Palma, Michela; Romeo, Emanuele; Sarubbi, Berardo
Abstract: Background: Pulmonary valve (PV) endocarditis is a frequent complication during follow-up in patients with repaired right ventricular outflow tract (RVOT) obstruction and poses relevant diagnostic and treatment challenges. We aimed to describe in details the possible different clinical presentations of this rare condition and to highlight the role of both transthoracic and transoesophageal echocardiography which, in experienced hands, may provide comprehensive useful information for the clinicians. Case summary: We below describe the clinical presentation and the echo findings of three cases of pulmonary valve endocarditis complicating disease course after different repair modalities of congenital right ventricular outflow tract obstruction. Discussion: The present case series outlines the diagnostic challenges of this increasingly frequent complication during follow-up of patients with congenital RVOT dysfunction after both surgical and percutaneous repair. Despite the diffusion of multimodality imaging, echocardiography with PV-dedicated views play a pivotal role in diagnosing such condition and guiding clinical management. Furthermore, this case series highlight that the suspicion of infective endocarditis should be raised whenever a sudden increase in transvalvular gradient is found during follow-up.